Desconsideração inversa da personalidade jurídica em processo trabalhista na Holding Familiar - Morello, Fernando José (2023)
The purpose of this article is to promote doctrinal and jurisprudential study regarding the possibility of (inverse) disregard of the legal personality affecting the assets of a family holding company constituted by the parents of a partner, executed in a labor action. To this end, doctrinal research was carried out regarding the types of existing holdings, their form of creation, capital constitution and possible clauses for use to protect assets. Furthermore, by verifying the relevant legislation and what doctrine and jurisprudence bring to the topic of disregarding (inverse) legal personality, the work brings about the construction of the major and minor theories provided for in substantive law. In addition, the way in which the incident was initiated to effect the disregard was verified in civil and labor procedural law and jurisprudential understandings were brought that corroborate the application of the minor theory in the labor field. With this, it was concluded that the (inverse) disregard of the legal personality can affect the assets donated by the founder of the family holding created as a form of succession planning.